Defining the Relationship Between Health and Well-being in Bioethics. Issue 1 (2nd January 2016) - Elliot, David
Abstract : Doctors and psychologists often use 'well-being' and 'quality of life' interchangeably, with quality of health overdetermining both. Insights from virtue ethics and St. Thomas Aquinas challenge this. Well-being has a primary 'eudaimonic' dimension, and an accompanying 'subjective' dimension. The 'eudaimonic' consists in a virtuous way of life in which our affective, cognitive, and other capacities are developed in pursuit of worthwhile aims. The 'subjective' consists in attaining and enjoying the goods necessary and fitting to a full human life. Does health — extended to include mental and physical health — account for the 'eudaimonic'? The result would problematically collapse ethics into medicine, and well-being into health. Rather, it is argued that health is a 'subjective' and not an 'eudaimonic' good, and that to a significant degree eudaimonic well-being can persist amid ill-health. Attending to the eudaimonic dimension helps us to overcome characteristic gaps in 'quality of life' discourse.